Quantification of Cerebrovascular Reactivity by Blood Oxygen Level–Dependent MR Imaging and Correlation with Conventional Angiography in Patients with Moyamoya Disease - Heyn, C.; Poublanc, J.; Crawley, A.; Mandell, D.; Han, J.S.; Tymianski, M.; terBrugge, K.; Fisher, J.A.; Mikulis, D.J. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: BOLD MR imaging combined with a technique for precision control of end-tidal pCO2 was used to produce quantitative maps of CVR in patients with Moyamoya disease. The technique was validated against measures of disease severity by using conventional angiography; it then was used to study the relationship between CVR, vascular steal, and disease severity. MATERIALS AND METHODS: A retrospective analysis comparing conventional angiography with BOLD MR imaging was performed on 11 patients with Moyamoya disease. Iso-oxic cycling of end-tidal pCO2 between 2 target values was performed during BOLD MR imaging. CVR was calculated as the BOLD signal difference per ΔpCO2. CVR was correlated with the presence of Moyamoya or pial collaterals and the degree of Moyamaya disease as graded by using a modified Suzuki score. RESULTS: A good correlation between mean CVR and Suzuki score was found for the MCA and ACA territories (Pearson correlation coefficient, −0.7560 and −0.6140, respectively; P < .0001). A similar correlation was found between mean CVR and the presence of pial and Moyamoya collateral vessels for combined MCA and ACA territories (Pearson correlation coefficient, −0.7466; P < .0001). On a voxel-for-voxel basis, there was a greater extent of steal within vascular territories with increasing disease severity (higher modified Suzuki score). Mean CVR was found to scale nonlinearly with the extent of vascular steal. CONCLUSIONS: Quantitative measures of CVR show direct correlation with impaired vascular supply as measured by the modified Suzuki score and enable direct investigation of the physiology of autoregulatory reserve, including steal phenomenon, within a given vascular territory. ACAanterior cerebral arteryAFNIanalysis of functional neuroimagesAIFarterial input functionANOVAanalysis of varianceBOLDblood oxygen level−dependentCBFcerebral blood flowCVRcerebrovascular reactivityCO2carbon dioxideΔSpCO2difference per change in end-title carbon dioxideffractionICAinternal carotid arteryMCAmiddle cerebral arterynegnegativePCAposterior cerebral arterypCO2partial pressure of carbon dioxidePETpositron-emission tomographypO2partial pressure of oxygenpospositiveSEstandard errorSPECTsingle-photon emission CTTIAtransient ischemic attack